Modelling and control of interlinking power converters in a hybrid AC/DC microgrid - Ye, Yuantao (2016)
The project is based on establishing a platform to convert AC to DC & DC to AC. The DC power can be integrated into existing AC power systems with the help of hybrid AC/DC microgrid. Hybrid AC/DC microgrids have been planned using in different generation power system by interconnection them, and made full of the features of both AC and DC microgrids. And the hybrid system includes AC and DC grid they are connected by interlinking bidirectional power converters. This is the main part to keep the whole system stable and reliable while operating. The project aims to design such a simulation models (hybrid micrigrid) using Matlab to achieve this function and also the controllers for maintaining the system stable when various disturbance comes into the system. Other models related to this power converter in the hybrid grid would also be modelled and evaluated. I worked a senior researcher to test the developed simulation models and control algorithms in a down-scaled lab test-bed. I need to design reversible PWM rectifier and its control of energy can be transferred on both directions. The PWM rectifier is different from other traditional rectifier. It has some advantages like: • The grid current will be sine wave • The grid side power is controlled by factor • The electric power is transferred both sides • Fast dynamic response